Sensitive Cloud Point Extraction Method for the Determination of Isoxsuprine Hydrochloride in Pharmaceutical forms using Spectrophotometry - Hind Hadi; Wasan A. Al-Uzri (College of Pharmacy University of Baghdad, 2022)
A simple and highly sensitive cloud point extraction process was suggested for preconcentration of micrograms amount of isoxsuprine hydrochloride (ISX) in pure and pharmaceutical samples. After diazotization coupling of ISX with diazotized sulfadimidine in alkaline medium, the azo-dye product quantitatively extracted into the Triton X-114 rich phase, dissolved in ethanol and determined spectrophotometrically at 490 nm. The suggested reaction was studied with and without extraction and simple comparison between the batch and CPE methods was achieved. Analytical variables including concentrations of reagent, Triton X-114 and base, incubated temperature, and time were carefully studied. Under the selected optimum conditions, the linearity ranges of calibration curves were 1-9 and 0.5-8 µg/mL with detection limits of 0.26 and 0.09 µg/mL of ISX for batch and CPE methods respectively. A relative standard deviation (RSD %) best than 1.98 and 2.67 % with the percentage recoveries range 100.14 and 99.63 % were obtained for both methods respectively. The proposed methods were successfully used in routine analysis of ISX in pharmaceutical forms with high accuracy and reproducibility.